PROPHYLACTIC DISPENSARY SCREENING OF DESIGNATED CONTINGENTS FOR BRUCELLOSIS - Mizrobov Doston Oktamovich (World Scientific Research Journal, 2025)
Abstract: In order to timely identify individuals infected with brucellosis, in accordance with the current directive of the Ministry of Health, individuals being employed as well as designated high-risk contingents must undergo mandatory annual prophylactic dispensary screening. This article outlines the general characteristics of brucellosis, including its etiology, epidemiology, methods of diagnosis and treatment, and strategies for improving prevention and epidemic control measures. The article also analyzes the main directions for reducing the spread of infectious diseases, based on global experience and modern approaches.